Notch signaling in lung diseases: focus on Notch1 and Notch3 - Dandan Zong; Ruoyun Ouyang; Jinhua Li; Yan Chen; Ping Chen (Therapeutic Advances in Respiratory Disease, 2016)
Notch signaling is an evolutionarily conserved cell–cell communication mechanism that plays a key role in lung homeostasis, injury and repair. The loss of regulation of Notch signaling, especially Notch1 and Notch3, has recently been linked to the pathogenesis of important lung diseases, in particular, chronic obstructive pulmonary disease (COPD), asthma, pulmonary fibrosis, pulmonary arterial hypertension (PAH), lung cancer and lung lesions in some congenital diseases. This review focuses on recent advances related to the mechanisms and the consequences of aberrant or absent Notch1/3 activity in the initiation and progression of lung diseases. Our increasing understanding of this signaling pathway offers great hope that manipulating Notch signaling may represent a promising alternative complementary therapeutic strategy in the future.